Social inequalities and representations of differences between the sexes - Poeschl, Gabrielle (2004)
This article summarises the academic debate on differences between the sexes and describes the opinions gathered on this by means of semi-structured interviews. Men give expression mainly to differences between individuals and women mainly to different positions in the public sphere; in evoking the personal sphere, unmarried men focus on the division of parental roles and married couples focus on the division of housework. The established relationship in the literature, between social position and personality traits, seems to be lacking in the representations of those interviewed, but the juxtaposition of their arguments enables us to understand the way each group contributes to the maintenance of social order.